Short-Term Repeated-Sprint Training in Hot and Cool Conditions Similarly Benefits Performance in Team-Sport Athletes - Périard, Julien D.; Pyne, David B.; Bishop, David J.; Wallett, Alice; Girard, Olivier (Frontiers in Physiology, 2020)
This study compared the performance and physiological adaptations of short-term repeated-sprint training in HOT (40ºC and 40% RH) and COOL (20ºC and 40% RH) conditions in team-sport athletes. Twenty-five trained males completed 5 training sessions of 60 min over 7 days in HOT (n=13) or COOL (n=12), consisting of a submaximal warm-up and 4 sets of maximal sprints. Before and after the intervention, intermittent shuttle running performance was assessed in cool and repeated-sprint ability in hot conditions, the latter preceded and followed by neuromuscular function testing. During the repeated-sprint training sessions skin (~8.4ºC) and core (~0.17ºC) temperature were higher in HOT than COOL (P<0.05). Shuttle running distance increased after both interventions (P<0.001), with a non-significant (P=0.131) but larger effect in HOT (315 m, d=1.18) than COOL (207 m, d=0.51). Mean (~7%, P<0.001) and peak (~5%, P<0.05) power during repeated-sprinting increased following both interventions, whereas peak twitch force before the repeated-sprint assessment was ~10% lower after the interventions (P=0.001). Heart rate during the repeated-sprint warm-up was reduced (~6 beats.min-1) following both interventions (P<0.001). Rectal temperature was ~0.14ºC lower throughout the repeated-sprint assessment after the interventions (P<0.001), with larger effects in HOT than COOL during the warm-up (P=0.082; d=-0.53 vs. d=-0.15) and repeated-sprints (P=0.081; d=-0.54 vs. d=-0.02). Skin temperature (P=0.004, d=-1.11) and thermal sensation (P=0.015, d=-0.93) were lower during the repeated-sprints after training in HOT than COOL. Sweat rate increased (0.2 L.h-1) only after training in HOT (P=0.027; d=0.72). The intensive nature of brief repeated-sprint training induces similar improvements in repeated-sprint cycling ability in hot conditions and intermittent running performance in cool conditions, along with analogous physiological adaptations, irrespective of the environmental conditions in which training is undertaken.